S56 Does time since arrival affect site of TB disease in UK migrants?. (14th November 2013) - Tamne, SK; Lalor, M; Thomas, L; Abubakar, I; Abubakar, I; Zenner, D
Abstract : Background: In contrast to global tuberculosis (TB) epidemiology, the UK and many low incidence countries have a high proportion of cases with extra-pulmonary tuberculosis (ETB). Almost 70% of reported cases in the UK are non-UK born, and many of these develop TB within the first five years after entry to the UK. The aim of the study was to analyse whether time since entry to the UK was associated with site of disease among migrants. Methods: All TB cases (n = 95, 427) reported to national enhanced TB surveillance system in the UK from 2000–2011 were included. In univariable analysis we explored associations between site of disease and place of birth, ethnic group, gender, age and previous TB diagnosis, using proportions and unadjusted odds ratios. Logistic regression was used to assess the association between site of disease and time since entry to the UK, adjusted for significant confounders. Results: A total of 86, 754 cases had complete information for site of disease and place of birth. Of these, 46, 284 (53%) cases had ETB increasing from 47% in 2000 to 58% in 2011. ETB was more common amongst the non-UK born (61%) compared with UK-born TB cases (36%). Cases who entered the UK more than one year ago were almost 3 times more likely to have ETB compared to UK born cases after adjusting for sex, age, ethnicity and previous TB diagnosis (aOR 2.98, 95% CI 2.89–3.07). Females (OR 1.22 95% CI 1.18–1.26), adults aged 30–60 years and individuals of black African/Indian subcontinent ethnicities were significantly more likely to have ETB. Conclusions: ETB was associated with being non-UK born, having entered the UK more than a year before diagnosis, female gender, age 30–60 years, and ethnic group. Conveying our findings to healthcare workers in the UK may improve awareness of ETB in specific populations, which could help lead to earlier diagnosis.